(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Dental anxiety is a prevalent issue that can significantly impact patients' willingness to seek necessary dental care, particularly for invasive procedures like endodontic treatment. Factors influencing dental anxiety include previous negative experiences, fear of pain, and the nature of the treatment itself. This study aims to explore the levels of pain and anxiety among Saudi patients prior to root canal treatment and identify variables influencing these levels. Objective: This study aimed to assess preoperative pain and anxiety levels in Saudi patients undergoing root canal treatment and to identify demographic and experiential factors that may affect these levels, ultimately providing recommendations for better management. Methods: A cross-sectional study was conducted from July to November 2024, involving 664 Saudi citizens aged over 18 who were scheduled for non-surgical root canal treatment. Participants were recruited through social media platforms. A structured questionnaire was administered to assess demographic information, pain and anxiety levels, and factors influencing these experiences. Pain and anxiety were scored on a scale of 1 to 10. Results: The average age of participants was 39.8 years, with a majority being married and well-educated. The median pain and anxiety scores were both 6, with 80.3% and 73.8% of respondents, respectively, rating their pain and anxiety levels above 4. Notably, 62.8% of patients reported using pain medication prior to treatment, while 75.5% had not used anxiety-relief medication. A significant proportion (51.4%) demonstrated low levels of awareness regarding the factors affecting pain and anxiety, suggesting a need for improved patient education. Conclusion: The study highlights the multifaceted nature of dental anxiety and pain perception among Saudi patients before endodontic treatment. Key findings indicate that while many patients experience significant anxiety and pain, a lack of awareness regarding the factors influencing these feelings persists. Enhanced educational interventions targeting these factors may improve patient experiences and treatment adherence, ultimately contributing to better oral health outcomes.